AMBER/VLTI Snapshot Survey on Circumstellar Environments. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Rivinius, Th.; de Wit, W.J.; Demers, Z.; Quirrenbach, A.; ,
Abstract: OHANA is an interferometric snapshot survey of the gaseous circumstellar environments of hot stars, carried out by the VLTI group at the Paranal observatory. It aims to characterize the mass-loss dynamics (winds/disks) at unexplored spatial scales for many stars. The survey employs the unique combination of AMBER's high spectral resolution with the unmatched spatial resolution provided by the VLTI. Because of the spatially unresolved central OBA-type star, with roughly neutral colour terms, their gaseous environments are among the easiest objects to be observed with AMBER, yet the extent and kinematics of the line emission regions are of high astrophysical interest.